2014
DOI: 10.1007/s11033-014-3820-3
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 up-regulation mediates glioblastoma cancer stem cells apoptosis and proliferation by targeting FASLG

Abstract: To investigate whether miR-21 can affect the apoptosis and proliferation of glioblastoma cancer stem cells (GSCs) from down-regulating FASLG. The expression of miRNA-21 was detected by quantitative real-time PCR in normal brain tissue and glioblastoma samples, and the changes of miRNA-21 expression between GSCs and non-GSCs were also detected. The apoptosis and proliferation ability of miR-21 in GSCs were analyzed by MTT and flow cytometry assay after anti-miR-21 transfection. For the regulation mechanism anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 20 publications
3
37
0
Order By: Relevance
“…MicroRNAs (miRNAs) belong to a class of small endogenous non-coding RNAs with $22nt that repress mRNA of protein-coding translation by base pairing of the target genes [4]. It has been shown that miRNAs regulate the expression of at least one-third of all human genes [5], and bioinformatics analyses estimate that more than 60% of human protein-coding genes maintain pairing to miRNAs with regulatory roles in cell proliferation, differentiation, apoptosis, pathogenesis of many human diseases and tumorigenesis [6][7][8][9][10][11]. The loss or dysregulation of certain individual miRNAs can have serious physiological consequences [12][13][14].…”
Section: T Cell Receptor (Tcr)abmentioning
confidence: 99%
See 3 more Smart Citations
“…MicroRNAs (miRNAs) belong to a class of small endogenous non-coding RNAs with $22nt that repress mRNA of protein-coding translation by base pairing of the target genes [4]. It has been shown that miRNAs regulate the expression of at least one-third of all human genes [5], and bioinformatics analyses estimate that more than 60% of human protein-coding genes maintain pairing to miRNAs with regulatory roles in cell proliferation, differentiation, apoptosis, pathogenesis of many human diseases and tumorigenesis [6][7][8][9][10][11]. The loss or dysregulation of certain individual miRNAs can have serious physiological consequences [12][13][14].…”
Section: T Cell Receptor (Tcr)abmentioning
confidence: 99%
“…Similarly, miR-21 is involved strongly in apoptosis inhibition, with targets belonging to both its intrinsic and extrinsic pathways [18]. FAS ligand (FASLG) was shown to be a miR-21 target in FASLG-mediated apoptosis tumorigenesis cell lines [9,18]. The axis FASLG/miR-21 may also represent an important molecular mechanism in ALPS-FAS pathophysiology, as soluble FASLG is augmented in patients [19].…”
Section: T Cell Receptor (Tcr)abmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects are mediated in part by decreased repression of targets including HNRPK, TAP63 , and PDCD4 37, 44, 46. Further, miR‐21 can modulate the extrinsic apoptotic pathway through downregulation of FASL , an ability that has been particularly evident in cancer stem cells 47. Thus, miR‐21 has widespread effects on cell death pathways, making it a critical player in GBM pathogenesis and a promising target for therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%